Adrenergic-pathway Gene Variants Influence β-Blocker-related Outcomes after Acute Coronary Syndrome in a Race-specific Manner - Cresci, Sharon (2012)
OBJECTIVE: Overcoming racial differences in acute coronary syndrome (ACS) outcomes is a strategic goal for US healthcare. Genetic polymorphisms in the adrenergic pathway appear to explain some outcome differences by race in other cardiovascular diseases treated with β-adrenergic receptor-blockade (BB). Whether these genetic variants are associated with survival among ACS patients treated with BB, and if this differs by race, is unknown. BACKGROUND: BB after ACS is a measure of quality care, but the effectiveness across racial groups, is less clear. METHODS: A prospective cohort of 2,673 ACS patients (2,072 Caucasian; 601 African Americans) discharged on BB from 22 U.S. hospitals were followed for 2 years. Subjects were genotyped for polymorphisms in ADRB1, ADRB2, ADRA2C, and GRK5. We used proportional hazards regression to model the effect of genotype on mortality, stratified by race and adjusted for baseline factors. RESULTS: The overall 2-year mortality rate was 7.5% for Caucasians and 16.7% for African Americans. The prognosis associated with different genotypes in these BB-treated patients differed by race. In Caucasians, ADRA2C 322-325 deletion (D) carriers had significantly lower mortality as compared with homozygous individuals lacking the deletion (HR 0.46; CI 0.21, 0.99; p=0.047; race-by-genotype interaction p= 0.053). In African Americans, the ADRB2 16R allele was associated with significantly increased mortality (HR for RG vs. GG =2.10; CI 1.14, 3.86; RR vs. GG =2.65; CI 1.38, 5.08; p=0.013; race-by-genotype interaction p=0.096). CONCLUSIONS: Adrenergic pathway polymorphisms are associated with mortality in ACS patients receiving BB in a race-specific manner. Understanding the mechanism by which different genes impact post-ACS mortality differently in Caucasian and African Americans may illuminate opportunities to improve BB therapy in these groups.